Learning and growing from 'communities of practice': autoethnographic narrative vignettes of an aspiring educational researcher's experience. Issue 1 (2nd January 2018) - Rådesjö, Megan
Abstract: This is an autoethnographic study that inquiries into my own journey as an aspiring educational researcher throughout the second course of my Master's Program at the University of Gothenburg in Sweden. My experiences take place in the context of a group of real educational researchers and their on-going research project at the faculty of education called 'Beyond Plant Blindness: Seeing the importance of plants for a sustainable world' (BPB). All of the experiences included in this study are expressed in the form of chronologically ordered narrative vignettes. In order to bring theoretical meaning to these experiences, the vignettes were critically reflected upon and interpreted through the concept Communities of Practice (CoP), which is central to situated learning theory. Through this conceptual lens, my experiences revealed that an aspiring educational researcher may feel emotional and intellectual growth as a newcomer who is granted legitimate peripheral participation in the 'real' researcher CoP. Consequently, this study sheds light on ways that real researchers may play a part in shaping the identities of aspiring educational researchers through learning experiences. However, more generally, this study may facilitate fresh conversations about the complexities of learning, identity, and inclusion in the field of educational research.